2018
DOI: 10.1177/0300891618792476
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil–lymphocyte ratio and platelet–lymphocyte ratio in rectal cancer patients following neoadjuvant chemoradiotherapy

Abstract: Elevated NLR and PLR levels can be considered as predictors of poor pathologic response, and NLR can be considered a prognosticator in patients who underwent neoadjuvant chemoradiotherapy for locally advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
6
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 30 publications
6
40
6
4
Order By: Relevance
“…To our knowledge, this is the largest reported study of the prognostic and predictive impact of NLR and/or PLR in this patient population. Previous studies have reported conflicting results in this setting, with some demonstrating poorer prognosis with higher NLR and/or PLR [39,40], while others did not observe any significant association [27]. Two prior meta-analyses investigating the prognostic role of NLR and PLR across a range of solid tumours demonstrated an association with adverse OS for both biomarkers in combined study populations of over 40,000 and 12,000 patients, respectively [19,20].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, this is the largest reported study of the prognostic and predictive impact of NLR and/or PLR in this patient population. Previous studies have reported conflicting results in this setting, with some demonstrating poorer prognosis with higher NLR and/or PLR [39,40], while others did not observe any significant association [27]. Two prior meta-analyses investigating the prognostic role of NLR and PLR across a range of solid tumours demonstrated an association with adverse OS for both biomarkers in combined study populations of over 40,000 and 12,000 patients, respectively [19,20].…”
Section: Discussionmentioning
confidence: 95%
“…With regard to their role in predicting response to neoadjuvant therapy, a recent systematic review and metaanalysis demonstrated an increased likelihood of pCR in patients with rectal cancer and low NLR receiving neoadjuvant chemotherapy +/− radiation (OR 2.01, 95% CI 1.14-3.55, p = 0.02) [42], which is inconsistent with our results. In addition, a recent study identified elevated PLR (> 133.4) to be a significant predictor of poor pathologic response in rectal cancer patients following nCRT [40]. The reasons for these discrepancies are unclear but may be related to differences in study design and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…NLR, PLR and MLR are known to be predictors of pathological response in LARC patients. Kim et al suggested that NLR<2.0 and PLR<133.4 before CRT were associated with better tumor response (26). Kim et al claimed that patients with baseline NLR>3 had poor tumor response (17), while…”
Section: Discussionmentioning
confidence: 99%
“…Data for eight blood-based measurements that had previously been reported in association with rectal cancer were collected. These included the neutrophil-to-lymphocyte ratio (20)(21)(22), platelet-to-lymphocyte ratio (20,21), lymphocyte-to-monocyte ratio (20,23), neutrophil-to-albumin ratio (24), serum albumin level (13), serum CEA level (14,15), hemoglobin concentration (25), and platelet count (26). The samples were acquired before the beginning of nCRT, and the results were standardized by linearly normalizing each feature to the range 0-1.…”
Section: Methodsmentioning
confidence: 99%